Bibliographie zur chinesischen Literatur in deutscher Sprache - Li, Xuetao 1965- (Geschichte der chinesischen Literatur, 2021)
Apart from Japan, no other country boasts as many translations of Chinese literature as Germany. This volume provides bibliographical access to this rich - and sometimes difficult to trace - body of translations throughout the ages